AB0685 The systemic lupus erythematosus activity scoring tool (LAST) and the simplified clinical index (C-LAST) are simple and sensitive indices of disease activity as compared to the sledai selena modification. (23rd January 2014) - Khraishi, M.; Aslanov, R.; Fudge, K.; Gu, M.; Lin, L.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with variable manifestations. New developments in the understanding and treatment of SLE mandated closer monitoring of the disease activity and its response to treatment. Current disease activity indices (e.g. SLEDAI SELENA, BILAG & SLAM) have their own limitations. Two new disease activity evaluation tools (the SLE Activity Scoring Tool (LAST) and the Clinical LAST (C-LAST)) were designed to simplify the approach in quantifying SLE activity while maintaining high sensitivity. An easy to use electronic application of these tools was also developed. Objectives: Primary: To validate two SLE activity tools with their correlation to the SLEDAI SELENA modification. Secondary: To test the usability and the accuracy of electronic applications of the same tools in clinical settings. Methods: The new disease activity tracking and evaluating tools included patient global assessment of disease activity (PGA), physician global assessment of disease activity (PHGA), and a formula incorporating the current immunomodulating medication used as an indication of SLE activity. The LAST included C3, C4 and Anti-ds Anti-DNA titer abnormalities as activity indicators. Patients who met the SLE ACR 1997 criteria update were seen in a rheumatology clinic during the last 12 months. The laboratory investigations were done within 2 weeks of their visit and the SLEDAI was evaluated for each visit. Five different algorithms of weighting the disease activity through different variables were calculated. Apple iPad and Windows web-based applications were developed for the LAST and C-LAST. Descriptive statistics and correlation bivariates (Pearson's & Spearman's) were conducted. Each algorithm result and multiple assessments of the disease activity were compared to the SLEDAI SELENA. Results: Twenty patients (90% females) with 38 assessments were included. Scores from 5 algorithms of the variables in addition to the SLEDAI SELENA scores were obtained at each visit. The mean (SD) age was 48.25 (15.17) years and the mean (SD) of disease duration was 12.35 (6.80) years. The mean (SD) SLEDAI score was 5.97 (4.12). The mean (SD) C-LAST and LAST (with C3, C4 and Anti-ds DNA) scores were 38.19 (19.27) and 35.32 (19.15), respectively. The correlation between the two new indices was very high: 0.925 with p=0.011. The correlation of the SLEDAI with both the LAST and the C-LAST was also significant (0.903 (p<0.001) and 0.766 (p<0.001), respectively). The SLEDAI scores were consistent with the LAST and C-LAST scores at the baseline and follow-up visits: from 0 to 4 corresponded up to 30; from 8 and higher were up to 50 and higher, respectively. The electronic applications of the LAST and C-LAST were easy to use and there were no errors detected in their results. Conclusions: The new disease activity tools correlated well with the SLEDAI SELENA modification. The use of simple clinical variables as a measure of SLE activity seemed to be valid. The development of easy to use electronic apps will make the usage of these activity tracking tools easier to calculate and possibly utilize in non-specialist settings. Disclosure of Interest: None Declared